Fairness and the goals of international criminal trials : finding a balance - Wheeler, Caleb H (New York: Routledge, 2023)
'This book presents a ground-breaking, interdisciplinary study into the various goals assigned to international criminal trials. It starts from the proposition that no hierarchy exists amongst the different goals meaning that trials should strive to achieve all of them in equal measure. This is made difficult by the fact that not all of these goals are compatible and the fulfilment of one may lead to others going unmet. Therefore, a balance must be found if the goals of trial are to be achieved at all. The book posits that fairness should serve as the guiding principle when weighing the different trial goals against one another. It is argued that without fairness international and internationalised criminal courts and tribunals lack legitimacy and without legitimacy they lack effectiveness. The book concludes that international criminal trials must adopt procedures that emphasise fairness to all of the parties and trial participants if they wish to accomplish any of the goals set for them. Each chapter is devoted to identifying and explaining a different trial goal, providing analysis of how that particular goal functions in conjunction with the other goals, and discussing the ways in which a fairness oriented trial model will help achieve those goals. The book provides a dynamic understanding of the different trial goals and the importance of fairness in the trial process by drawing on research from a variety of different legal disciplines while also incorporating scholarship rooted in criminology, political theory, international relations, and psychology. The book will be essential reading for researchers, academics and professionals working in the areas of International Criminal Law, Public International Law and Transitional Justice'--
The role fairness plays in legal accountability -- International criminal trials and promoting the rule of law -- International criminal trials and the search for truth -- Peace, justice, and international criminal trials -- How international criminal trials can encourage reconciliation -- Achieving the goal of providing the victims of atrocity crimes with justice.
Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ Pemilihan Ketua Perpustakaan Undang-Undang/ CIP/ Areesh Education & Trading
Includes bibliographical references and index.
Keywords: International criminal courts; Fair trial; War crime trials; Trials (Crimes against humanity).; Criminal procedure (International law).